Probing Mass Transfer in Mesoporous Faujasite‐Type Zeolite Nanosheet Assemblies. Issue 8 (20th March 2014) - Mehlhorn, Dirk; Inayat, Alexandra; Schwieger, Wilhelm; Valiullin, Rustem; Kärger, Jörg
Abstract Pulsed field gradient nuclear magnetic resonance (NMR) diffusion studies are performed by using cyclohexane to probe transport properties in a NaX‐type zeolite with a hierarchical pore structure (house‐of‐cards‐like assemblies of mesoporous nanosheets), which is compared with a purely microporous sample. With guest loadings chosen to ensure saturation of the micropores, and the meso‐ and macropores left essentially unoccupied, guest diffusion is shown to be enhanced by almost one order of magnitude, even at room temperature. Diffusivity enhancement is further increased with increasing temperature, which may, therefore, be unambiguously attributed to the contribution of mass transfer in the meso‐ and macropores.